Ineffectiveness of Industrial Relations Court Decision Execution: A Critical Analysis of Procedural Law Vacuum and the Urgency of Establishing a Special Execution Institution - Herdiana, Dadan; Ekawati, Dian; Santini, Inawati (SIGn Journal of Social Science, 2025)
The development of labor law in Indonesia aims to achieve social justice by protecting workers’ rights. However, the reality of law enforcement reveals a juridical anomaly in which Industrial Relations Court decisions that have obtained permanent legal force (inkracht van gewijsde) are frequently not executed (non-executable). Consequently, workers’ normative rights, such as the right to severance pay and unpaid wages, remain unfulfilled. This study aims to analyze the root causes of such execution failures and to formulate effective institutional solutions. Utilizing a normative juridical research method with statutory, conceptual, and case approaches, this research examines the dependence of Law Number 2 of 2004 on the Civil Procedure Law—specifically the HIR/RBg—which is passive and formalistic in nature. The results indicate that execution failure is caused by the burden of asset proof being placed entirely on the worker. Furthermore, the absence of the court’s investigative authority to conduct asset tracing, along with judges’ weak application of Conservatory Attachment (Conservatoir Beslag) and Penalty Payments (Dwangsom), exacerbates the situation. Dependence on the archaic HIR/RBg procedures proves incompatible with the characteristics of labor disputes that demand speed. This is worsened by the dynamics of non-standard employment relationships in the gig economy, which are vulnerable to asset stripping. This study concludes that without procedural law reform, Industrial Relations Court decisions remain merely illusory judgments. Therefore, the establishment of a Special Execution Unit within the Industrial Relations Court, with autonomous authority to access integrated asset data, is recommended. Additionally, the issuance of regulations mandating the application of Dwangsom on an ex officio basis in every condemnatory (condemnatoir) decision is necessary to guarantee legal certainty and substantive justice for workers.